The Structure and Semantics of Al-Idhafah in Safinatu al-Shalah by Imam Abdullah bin Umar al-Hadrami: A Syntactic-Semantic Study - Supriyadi, Moh.; Rauf, Abdur (Dzil Majaz: Journal of Arabic Literature, 2025)
The grammatical construction known as Al-Idhafah (annexation/genitive construction) refers to a syntactic relationship between two nouns, where the second noun (the mudhaf ilayh) defines or restricts the first noun (the mudhaf). However, idafah is not merely a combination of two nouns; it often carries implicit prepositional meanings, such as possession (of), origin (from), or association (about), making it essential for accurate sentence interpretation. Misunderstanding this structure may lead to errors in speaking, reading, and writing. This study explores how idafah is used and what meanings it conveys in the classical Islamic text Safinatu al-Shalah ("The Ark of Prayer") authored by Imam Abdullah bin Umar bin Yahya al-Hadrami—a well-known text in basic Islamic jurisprudence (fiqh). The research aims to answer the following questions: What are the words that include idafah constructions in Safinatu al-Shalah? And what are the semantic meanings conveyed by these constructions? To achieve this, the study employs a descriptive qualitative method with a library research approach. The primary data source is the book Safinatu al-Shalah, while secondary sources include grammatical references and linguistic studies. Data collection was conducted through careful reading and note-taking, and analysis was carried out descriptively. The results show that the text frequently employs idafah to convey meanings such as possession (who), origin (from), and aboutness (about). This highlights the significance of idafah as a crucial grammatical device in Arabic for precise meaning and clear communication, especially in religious and legal discourse.